Use of intravenous epoprostenol as a treatment for the digital vasculopathy associated with the scleroderma spectrum of diseases. Issue 3 (September 2017) - Law, Shing T.; Farber, Harrison W.; Simms, Robert W.
Introduction: Intravenous prostanoid therapy is recommended for severe systemic sclerosis-related digital vasculopathy. The evidence supporting this recommendation is limited. The aim of this study was to evaluate the safety and efficacy of treating scleroderma spectrum digital vasculopathy with intravenous epoprostenol. Methods: Patients with a diagnosis of systemic sclerosis who had received intravenous epoprostenol for scleroderma spectrum digital vasculopathy between 1 st October 2003 and 1 st September 2015 at Boston University Medical Center were identified using ICD-9 code search, and their charts were reviewed in this retrospective case series. Results: Of 47 encounters for intravenous epoprostenol infusion for scleroderma spectrum digital vasculopathy, 29 had documentation of improvement as indicated by any of the following: pain relief, increased perfusion of digits as assessed by warmth or color, reduced digital ulcer number or size. In 16 encounters, there was no documentation on whether the indicative condition had improved. No deterioration of the indicative condition was documented in any encounters. Intravenous epoprostenol infusion was well tolerated with few significant adverse effects. Conclusions: Intravenous epoprostenol infusion in the treatment of scleroderma spectrum digital vasculopathy is safe. The condition improved with intravenous epoprostenol infusion, although there were study design constraints. We describe our protocol for administering intravenous epoprostenol infusion for scleroderma spectrum digital vasculopathy to improve consistency of patient care.